HDACs Regulate miR-133a Expression in Pressure Overload–Induced Cardiac Fibrosis. (November 2015) - Renaud, Ludivine; Harris, Lillianne G.; Mani, Santhosh K.; Kasiganesan, Harinath; Chou, James C.; Baicu, Catalin F.; Van Laer, An; Akerman, Adam W.; Stroud, Robert E.; Jones, Jeffrey A.; Zile, Michael R.; Menick, Donald R.
Abstract : Background—: MicroRNAs (miRNAs) and histone deacetylases (HDACs) serve a significant role in the pathogenesis of a variety of cardiovascular diseases. The transcriptional regulation of miRNAs is poorly understood in cardiac hypertrophy. We investigated whether the expression of miR-133a is epigenetically regulated by class I and IIb HDACs during hypertrophic remodeling. Methods and Results—: Transverse aortic constriction (TAC) was performed in CD1 mice to induce pressure overload hypertrophy. Mice were treated with class I and IIb HDAC inhibitor (HDACi) via drinking water for 2 and 4 weeks post TAC. miRNA expression was determined by real-time polymerase chain reaction. Echocardiography was performed at baseline and post TAC end points for structural and functional assessment. Chromatin immunoprecipitation was used to identify HDACs and transcription factors associated with miR-133a promoter. miR-133a expression was downregulated by 0.7- and 0.5-fold at 2 and 4 weeks post TAC, respectively, when compared with vehicle control ( P <0.05). HDAC inhibition prevented this significant decrease 2 weeks post TAC and maintained miR-133a expression near vehicle control levels, which coincided with (1) a decrease in connective tissue growth factor expression, (2) a reduction in cardiac fibrosis and left atrium diameter (marker of end-diastolic pressure), suggesting an improvement in diastolic function. Chromatin immunoprecipitation analysis revealed that HDAC1 and HDAC2 are present on the miR-133a enhancer regions. Conclusions—: The results reveal that HDACs play a role in the regulation of pressure overload–induced miR-133a downregulation. This work is the first to provide insight into an epigenetic-miRNA regulatory pathway in pressure overload–induced cardiac fibrosis. Abstract : Supplemental Digital Content is available in the text.